Study on the control method of flatness of thin-walled parts milled from 7075 aluminum alloy based on ice-fixation - Gang Jin; Qiyun Zhan; Wenshuo Li; Zhanjie Li; Huaixin Lin (International Journal of Lightweight Materials and Manufacture, 2023)
Investigation of a new process and method to control the planarity of thin-walled parts can provide an important theoretical and application foundation for the high-precision, high-quality fabrication of thin-walled components in aerospace and other areas. A planarity control method based on ice fixation for the milling of thin-walled parts is proposed for thin-walled aluminum alloy 7075 flat parts. The heart of the method is the application of a low temperature of about −5 °C to a flat thin-walled part using a freezing tray to hold the workpiece in place in order to control the flatness of the thin wall face grinding process. Investigation of the influence of the machining process and workpiece shape parameters on the machining flatness of thin-walled parts was conducted based on the practicality and efficiency of the method. Experimental results demonstrate that: compared to traditional milling (non-ice fixation), this method of fixing the ice can significantly improve the milling flatness of thin-walled parts, with the reduction of flatness ranging from 16.4% to 60.0%; however, the reduction of flatness is accompanied by the phenomenon of increasing milling force, with the mean increase in milling strength ranging between 5.8% and 40.3%; the flatness of the machining process decreases with increasing workpiece thickness (15.6%–65.0%) and increases with an increasing aspect ratio of the workpieces (17.4%–48.7%). The orthogonal test results show that the best-machined flatness can be achieved at large spindle speed, high feed rate, and low cutting depth working conditions, i.e. spindle speed 3000r·min−1, feed rate 350  mm·min−1, and cutting depth 0.01 mm.